1981
DOI: 10.1203/00006450-198110000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Weight Reduction in Young Obese Children. I. Effects on Adipose Tissue Cellularity and Metabolism

Abstract: SummaryA 10-year longitudinal study was conducted on 26 prepubescent youngsters who had undergone successful weight reduction. Their ages ranged from 2 to 10 years when the study began. In all subjects, weight reduction proceeded only by a decrease in adipose cell size (from 0.62 + 0.02 to 0.46 k 0.02 pg lipid per cell) and resulted in a corresponding 33% decrease (from 177 + 6 to 144 + 5%) in percent ideal body weights. Cell numbers did not change appreciably during the period of weight loss (29.4 k 2.6 versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…These changes are even larger in obesity syndrome that is mainly characterized by fat cell hypertrophy. 3 In adipose tissue from obese animals or humans, several metabolic functions are subject to change with adipocyte size. These functions include storage and mobilization of lipids, 4,5 and secretion of both leptin 6 and tumour necrosis factor a (TNFa).…”
Section: Introductionmentioning
confidence: 99%
“…These changes are even larger in obesity syndrome that is mainly characterized by fat cell hypertrophy. 3 In adipose tissue from obese animals or humans, several metabolic functions are subject to change with adipocyte size. These functions include storage and mobilization of lipids, 4,5 and secretion of both leptin 6 and tumour necrosis factor a (TNFa).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 New adipocytes arise in the process of di¡erentiation of preadipocytes. Studies have shown that an increase in fat-cell number appears to be well correlated with the severity of human obesity in adult life, 1 and speci¢c early di¡erentia-tion genes have been reported to be expressed in adipose tissue from very old mice.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have demonstrated a hyperplastic component to obesity. For example, sequential biopsies in children indicate that fat cell numbers increase when body fat reaches 25% of total weight (26,35). Similarly, obese adults have increased numbers of fat cells (30), and preadipocytes from obese subjects proliferate more rapidly in culture than cells from lean individuals (30,51).…”
mentioning
confidence: 99%